Key Technology of Distributed E-commerce System Architecture - Guo Xiaohui; Gao Rong; Wei JianYu; Huo Chongning (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A new distributed E-commerce architecture is put forward in the study, through the careful analysis of the existing shortcomings of the architecture of the present E-commerce system. The system integrates multi-commercial activities of E-commerce under the loose-coupled service programs so that the architecture of large scale distributed E-commerce system is formed. The trans-regional distributed E-Commerce architecture aims at solving the urgent problems such as resource recomposition and distributed deployment ahead of large commerce systems. Based on it, we propose the global scheme that could be built in the agent-based P2P network or other environment, and the latest software technologies could be used in the servers to publish the cooperation services. As far as the present technology is concerned, Web service P2P and agent technology are good choice, which are the three key supporting technologies of the architecture. Each branch market can be operated and maintained independently regardless of the existence of others, but their order services are to be centrally processed by the order server. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4346